Parasitism in aquatic ecosystems of Urabá: potential risks in wild fish and their relationship with aquaculture production - Carrillo-Bonilla, Lina; Caicedo, María Camila; Perea, Santiago; Barrios, María Lila (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Aquaculture is a key activity for food security and rural economies in Urabá, Antioquia. However, small-scale systems can be compromised by parasitic infections that reduce productivity and pose zoonotic risks, particularly due to the coexistence of wild fish, farmed fish, and domestic animals, especially in artisanal farming systems. This study aimed to analyze farmed and wild fish in this region of Colombia. Objective: To assess the presence of trematode parasitic species in wild fish from Urabá and their potential effects on small-scale rural aquaculture. Methodology: Sampling was conducted in rural aquaculture farms, wild fish populations, and domestic animals near these systems. Helminth species were identified using morphological and molecular techniques. Results: In wild fish populations, Clinostomum sp., Proterodiplostomum sp., and one acanthocephalan were identified, whereas no parasites were detected in farmed Oreochromis niloticus. Although no parasite transmission was observed between wild and farmed fish, the use of natural water sources in some aquaculture systems may represent a potential pathway for parasite introduction. In addition, forms compatible with Fasciola hepatica were detected in Brycon henni. Given the unusual nature of this finding, considering that this trematode typically infects mammalian hosts, it should be interpreted with caution and corroborated by further studies. Conclusion: Although no parasites were detected in farmed tilapia, the high prevalence of trematodes in wild fish confirms zoonotic risks that demand permanent monitoring at the wildlife–aquaculture interface. The sustainability of rural aquaculture in Urabá depends on continuous surveillance and sanitary control strategies to safeguard production and public health.